2013
DOI: 10.3892/or.2013.2826
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of LGR5 suppresses the proliferation of glioma cells in vitro and in vivo

Abstract: Leucine-rich repeat containing G protein-coupled receptor 5 (LGR5), one of the target genes of the Wnt signaling pathway, has recently been identified as a marker for brain cancer stem-like cells. However, the role of LGR5 in glioma is poorly understood. The aim of the present study was to investigate the relationship between LGR5 expression and pathological grade in glioma, and the impact of LGR5 on the proliferation of glioma cells in vitro and in vivo. Firstly, LGR5 expression was immunohistochemically eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…3 ), suggesting that LGR5 accelerates the cell cycle in cervical cancer cells. All of our findings together indicate that LGR5 functions to promote the development and progression of cervical cancer, consistent with previous reports in basal cell carcinoma[ 18 ] and malignant glioma[ 40 ]. However, Walker F et al reported an inhibitory effect of LGR5 on cell proliferation in colorectal cancer[ 41 ], suggesting that LGR5 may have different impacts on different types of carcinomas.…”
Section: Discussionsupporting
confidence: 93%
“…3 ), suggesting that LGR5 accelerates the cell cycle in cervical cancer cells. All of our findings together indicate that LGR5 functions to promote the development and progression of cervical cancer, consistent with previous reports in basal cell carcinoma[ 18 ] and malignant glioma[ 40 ]. However, Walker F et al reported an inhibitory effect of LGR5 on cell proliferation in colorectal cancer[ 41 ], suggesting that LGR5 may have different impacts on different types of carcinomas.…”
Section: Discussionsupporting
confidence: 93%
“…This data indicated that LGR5 may have a role in the regulation of CRC cell growth and proliferation, which is consistent with the results of previous investigations into basal cell carcinoma (15), Ewing sarcoma (24) and glioma (38). Thus, LGR5 may have the potential to serve as a therapeutic target in patients with CRC.…”
Section: Discussionsupporting
confidence: 80%
“…Whereas several studies have shown that LGR5 is important for glioblastoma CSC function and patient survival (Nakata et al, 2013; Parry and Engh, 2014; Wang et al, 2014), the role of ABCG1 in glioma pathogenesis is unknown. ABCG1 is a member of a large superfamily of membrane-bound ATP-binding cassette (ABC)-containing proteins important for cellular transport (Tarling and Edwards, 2011; Wang et al, 2004), where it directs lipid transport (Kennedy et al, 2005; Klucken et al, 2000).…”
Section: Resultsmentioning
confidence: 99%